Sistem Pendukung Keputusan Penentuan Surveyor Terbaik Menerapkan Algoritma Iterative Dichotomizer 3 - Rikki Ramadan Saragih; Natalia Silalahi (JURIKOM (Jurnal Riset Komputer), 2020)
The surveyor has the task of conducting surveys or supervising the main object of other work, while the other work is the marketing objective of the Bank. The importance of the surveyor for the company so that all transactions that will be carried out by the debtor do not experience problems or the term is bad credit. Bank Mandiri Syariah sometimes gets results that cannot guarantee the success of the payment period from prospective debtors, this is due to the possibility of disobedience of survey officers to work properly, thus of course detrimental to Bank Mandiri Syariah Medan. Bank Mandiri Syariah Medan provides a career path for survey officers to become Supervisor Surveyors. The determination of the best surveyor is carried out by processing the data according to the types of criteria used as the reference standard in Bank Mandiri Syariah Medan. The application of the Iterative Dichotomizer 3 algorithm for the process of determining the best surveyor is carried out by defining the limits of the value of the input variable.